A study on adverse drug reactions to non-ionic contrast medium in an Indian population: a 1-year experience - Bhowmick, Subhrojyoti; Bhat, Esha; Panja, Buddhadev; Mukherjee, Satarupa; Sikdar, Shreya; Biswas, Arnab; Ejaz, A. Bari; Chatterjee, Tapan K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To the best of our understanding, very few studies focusing on the adverse drug reaction (ADR) profile of non-ionic contrast medium (NICM) has been carried out until date among the Indian population. Hence, this study was planned. We sincerely believe that the knowledge gathered from this study can improve safer usage of these agents among the patients of Indian origin. The objective was to evaluate the incidence and severity of ADRs of non-ionic radio contrast media (CM) used in tertiary care hospital in Eastern India. Methods: For the duration of 1-year from July 2011 to July 2012, we prospectively recorded all the ADRs associated with the administration of NICM (iohexol and ioversol) in 3708 patients of Indian origin undergoing computed tomography scan at the hospital. The average median age, weight, dose used; types of ADRs, concomitant medication, final diagnosis, reasons for use were recorded and analyzed with appropriate statistical tools. Causality assessment was performed using Naranjo scale. Results: Eleven of 3708 patients who received either ioversol or iohexol developed ADRs (i.e. 0.3% of patients). The most common ADR was rigor. The incidences of mild, moderate and severe reactions were 55%, 36% and 9%, respectively. Average median age, weight, and dose used were 35 years, 66 kg and 70 ml, respectively. All the ADRs were early (occurred within 1 hr of CM administration). Due to logical constraints, the follow-up of these patients was not possible and hence late ADRs were not captured. The common concomitant medication used was pantoprazole (63.63% of patients). The difference in the incidence of ADRs by age distribution (Group 1 - Iohexol, Group 2 - Ioversol) and weight distribution was not statistically significant (p=0.75 and p=0.18, respectively). Causality analysis revealed that all the ADRs were possible (Score of 4). Interestingly, the incidence of reactions was noted to be higher in patients with a history of gastro intestinal disorders (45.45%). Conclusions: This pilot study reveals that adverse reactions to NICM are rare and severe reactions are less common among the patients of Indian origin. However, a larger multicentric study across the country should be carried out to understand the safety profile of these CM better among the Indian population.